PENGARUH IKLIM ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI PADA TK IT IBNU HAJAR DOMPU - Irwansyah; Nurhalizah, Siti; Subhan, Ega Saiful; Mahmud, Mahmud (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2024)
This study aims to determine the influence of organizational climate and commitment on employee performance at TK IT Ibnu Hajar Dompu. Associative quantitative research method, with saturated sample techniques, with as many as 34 employees. The questionnaire is the main data collection technique and is supported by observation, documentation, interviews, and literature studies. The data analysis technique uses SPSS v.25. The study results found a positive and significant influence between the variables of organizational climate and organizational commitment on employee performance through the t-test, while the f-test shows that both independent variables have a positive and significant effect together. This shows that the better the organizational climate and commitment, the more it will improve employee performance. The results of this study imply that the leadership of TK IT Ibnu Hajar Dompu in improving employee performance must start with efforts to improve organizational climate and commitment to compete.